Synthesis of Spin-Labeled Ibuprofen and Its Interaction with Lipid Membranes - Denis S. Baranov; Anna S. Smorygina; Sergei A. Dzuba (Molecules, 2022)
Ibuprofen is a non-steroidal anti-inflammatory drug possessing analgesic and antipyretic activity. Electron paramagnetic resonance (EPR) spectroscopy could be applied to study its interaction with biological membranes and proteins if its spin-labeled analogs were synthesized. Here, a simple sequence of ibuprofen transformations—nitration, esterification, reduction, Sandmeyer reaction, Sonogashira cross-coupling, oxidation and saponification—was developed to attain this goal. The synthesis resulted in spin-labeled ibuprofen (ibuprofen-SL) in which the spin label TEMPOL is attached to the benzene ring. EPR spectra confirmed interaction of ibuprofen-SL with 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) bilayers. Using 2H electron spin echo envelope modulation (ESEEM) spectroscopy, ibuprofen-SL was found to be embedded into the hydrophobic bilayer interior.